Intercropping buckwheat with squash to reduce insect pests and disease incidence and increase yield. Issue 8 (13th September 2016) - Razze, Janine M.; Liburd, Oscar E.; Webb, Susan E.
ABSTRACT: Aphids and whiteflies are significant direct pests of squash and transmit plant viruses. The use of buckwheat, Fagopyrum esculentum Moench, as a living mulch intercropped with squash has been shown to reduce insect pests and diseases while increasing the abundance of beneficial insects; however, how to best implement buckwheat in squash fields has not been determined. Several arrangements of intercropping buckwheat and squash were evaluated, with and without the introduction of a natural enemy, Delphastus catalinae (Horn), to find a tactic that reduces insect pests and disease incidence while increasing marketable yield. Intercropping treatments included planting strips of buckwheat alternating on either side of the squash with and without D. catalinae (arrangement A), planting buckwheat in the middle of squash planted on both sides of the bed with and without D. catalinae (arrangement B), buckwheat planted on both sides of squash (arrangement C), and a bare ground treatment. Aphid densities and insect-transmitted viruses were reduced, while natural enemies were more abundant, in buckwheat treatments compared with bare ground treatments. Plant size was reduced in intercropping arrangements B and C compared with arrangement A. Marketable yields were not different between the bare ground treatment and buckwheat arrangements A and B.